Advances in and the future of treatments for hepatitis C. (August 2014) - Cheng, Robert; Tu, Thomas; Shackel, Nicholas; McCaughan, Geoffrey W
<x xml:space="preserve">Abstract</x> Enormous progress has been made in the understanding of the hepatitis C virus and the development of novel therapeutic agents since the identification of the virus 25 years ago. From initial interferon monotherapy providing only 6% viral clearance rate in the 1980s, pharmacotherapeutics has now entered an exciting new era with direct-acting antiviral agents demonstrating viral clearance rates of more than 70%. We are now at the beginning of an era where combinations of direct-acting antiviral agents may pave the way for interferon-free regimens, even improving the viral clearance rate to near 100%.